Patriarchal Society and Women's Oppression in Margret Atwood's the Handmaids Tale: A Feminist Study (The Peerian Journal, 2024)
In this study, feminism theory is used to analyze the text. According to the investigation, the handmaids were mistreated by the Masculine in three different ways. First, Masculine seizes their possessions, wealth, and employment; second, once they lose their authority, Masculine seizes control of their bodies and exploits them; and third, Masculine restricts their actions in order to keep them in domestic duties. These methods are put into practice on the system using the tools of economics, sociology, and psychology as well as religion.